2021
DOI: 10.1111/jgs.17183
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Medicare beneficiaries with dementia

Abstract: Background/Objectives No data exist regarding the validity of International Classification of Disease (ICD)‐10 dementia diagnoses against a clinician‐adjudicated reference standard within Medicare claims data. We examined the accuracy of claims‐based diagnoses with respect to expert clinician adjudication using a novel database with individual‐level linkages between electronic health record (EHR) and claims. Design In this retrospective observational study, two neurologists and two psychiatrists performed a st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 29 publications
0
51
0
Order By: Relevance
“…Most studies that detected cognitive decline used structured EHR data and focused on later stages of cognitive decline. 10 , 11 , 12 , 22 Two studies used free-text notes for detecting MCI and/or dementia. 11 , 12 The first used the Mayo Clinic Study of Aging population to assess keyword search for identifying patients with cognitive impairment and dementia among intensive care unit patients who received formal cognitive evaluation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies that detected cognitive decline used structured EHR data and focused on later stages of cognitive decline. 10 , 11 , 12 , 22 Two studies used free-text notes for detecting MCI and/or dementia. 11 , 12 The first used the Mayo Clinic Study of Aging population to assess keyword search for identifying patients with cognitive impairment and dementia among intensive care unit patients who received formal cognitive evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies primarily focused on the stages of cognitive decline from MCI to dementia. 10 , 11 , 12 Limited research has focused on detection of early cognitive decline preceding MCI or use of unstructured EHR data (clinical notes).…”
Section: Introductionmentioning
confidence: 99%
“…Several algorithms have been developed for phenotyping cognitive status; some studies used structured data, such as diagnosis codes, missed appointments, or health care utilization patterns [ 15 , 23 ], whereas others have applied natural language processing (NLP) to unstructured notes [ 18 , 19 , 24 ]. None of these prior efforts combined both structured and unstructured input modalities, and manual annotation by clinical experts is limited by the lack of available tools to facilitate efficient chart review [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…It highlights key information and presents a summarized view to the annotator. We evaluated NAT in two EHR data sets: (1) Medicare beneficiaries from the Mass General Brigham (MGB) Accountable Care Organization (ACO) who were labeled in another study using manual chart reviews [ 15 ] and (2) MGB patients with laboratory confirmed SARS-CoV-2 (a case-control study to investigate the effects of COVID-19 on people with and without HIV was used as an exemplar of a research cohort that requires labeling of cognitive status). We evaluated interrater agreement in the first data set and compared it to interrater agreement in Epic—the EHR system used at MGB since 2015.…”
Section: Introductionmentioning
confidence: 99%
“…This bias would likely underestimate the magnitude of the disparity in dementia rates between PWH and PWoH. Furthermore, dementia adjudication using ICD codes increases diagnostic error [32,33], and it is uncertain whether there may exist biases or differential attribution of dementia by clinicians to PWH vs. PWoH. Studies dedicated to evaluate cognition in PWH may help clarify these uncertainties.…”
mentioning
confidence: 99%